Heat waves in spring from Senegal to Sahel: Evolution under climate change. (19th May 2021) - Sambou, Marie‐Jeanne Gnacoussa; Pohl, Benjamin; Janicot, Serge; Landry Famien, Adjoua Moïse; Roucou, Pascal; Badiane, Daouda; Gaye, Amadou Thierno
Abstract: This study analyses the long‐term (1950–2100) observed and projected changes in springtime (March–May) heat waves (HWs) in West Africa under climate change. To that end, 28 climate models participating to the fifth Coupled Model Intercomparison Project (CMIP5) are considered, after a statistical post‐correction of their biases. A multi‐scale approach is proposed, covering the Sahel, Senegal, and three thermally‐coherent zones within Senegal. HWs are defined as a sequence of at least three consecutive days above a moving 95th percentile of current temperature distributions. Climate change over Senegal translates into a general shift of the whole statistical distribution towards higher temperature values, with a general stability in the shape of the distribution. Ongoing mean warming could reach +5°C in 2100 under RCP8.5 scenario, implying that coastal Senegal could experience then a mean climate comparable to the hinterland parts today. HWs have increased in intensity, frequency and duration across Sahel and Senegal over the past years, such intensification being higher on recent decades. Future HWs over all regions present intrinsic properties that radically differ from those observed so far. The severity and length of HWs displayed stationary conditions until the late 1990s, but started increasing since then. Projected changes show marked and rapid increase in these variables, the amplitude of which is primarily RCP‐dependent, and secondarily region‐dependent. For both metrics, the largest changes occur over hinterland Senegal and Sahel. There, under RCP8.5 and after the 2070s, the whole spring season could be considered as a permanent HW lasting 3 months. Along the coast, by contrast, average temperatures are both weaker and more variable, causing more frequent threshold crossings and limiting the duration of HWs. The multi‐scale approach used here highlights contrast within Senegal, which constitutes important information for public policy decision‐makers and its inhabitants in terms of adaptation to climate change. Abstract : A multi‐scale approach of heat wave evolution in spring under climate change is proposed from Senegal to Sahel, including three coherent zones within Senegal, by using bias‐corrected climate projections from 28 climate models (1, 2). Temporal evolution of multi‐model values of heat waves characteristics shows a contrasted evolution according to the climate scenarios (3).